Pertanggungjawaban Pidana Korporasi atas Pencemaran dan Perusakan Lingkungan: Studi Normatif terhadap Prinsip Strict Liability di Indonesia - Rafli Ramdani; Chandra Devaraihan Wahyudi; Sultan Novaliyana Putra (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
Corporations play a vital role in economic development, yet massive industrialization often negatively impacts environmental sustainability. This article examines the legal construction of corporate criminal liability in environmental crimes in Indonesia. The research focuses on the paradigm shift from